2000
DOI: 10.1021/bi991797d
|View full text |Cite
|
Sign up to set email alerts
|

Reactions of Pseudomonas 7A Glutaminase-Asparaginase with Diazo Analogues of Glutamine and Asparagine Result in Unexpected Covalent Inhibitions and Suggests an Unusual Catalytic Triad Thr-Tyr-Glu,

Abstract: Pseudomonas 7A glutaminase-asparaginase (PGA) catalyzes the hydrolysis of D and L isomers of glutamine and asparagine. Crystals of PGA were reacted with diazo analogues of glutamine (6-diazo-5-oxo-L-norleucine, DON) and asparagine (5-diazo-4-oxo-L-norvaline, DONV), which are known inhibitors of the enzyme. The derivatized crystals remained isomorphous to native PGA crystals. Their structures were refined to crystallographic R = 0.20 and R(free) = 0.24 for PGA-DON and R = 0.19 and R = 0.23 for PGA-DONV. Differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
65
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(66 citation statements)
references
References 14 publications
(32 reference statements)
1
65
0
Order By: Relevance
“…Instead, a threonine residue located in a flexible loop near the N terminus is used as the primary nucleophile by 2 H. D. Becker, personal communication. asparaginases (17,18), and a well conserved Thr-Asp-Lys triad is found in the substrate-binding pocket (14,15). Sequence analysis indicated that these active site residues are also conserved in GatD, and Thr-101, Thr-177, Asp-178, and Lys-254 in M. thermautotrophicus GatD may be important for asparagine/ glutamine recognition (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Instead, a threonine residue located in a flexible loop near the N terminus is used as the primary nucleophile by 2 H. D. Becker, personal communication. asparaginases (17,18), and a well conserved Thr-Asp-Lys triad is found in the substrate-binding pocket (14,15). Sequence analysis indicated that these active site residues are also conserved in GatD, and Thr-101, Thr-177, Asp-178, and Lys-254 in M. thermautotrophicus GatD may be important for asparagine/ glutamine recognition (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies used intein-based chemistry to add electrophilic moieties such as vinyl methyl ester to the C terminus of ubiquitin to covalently trap nucleophilic cysteines in deubiquitinases. Because Dop has glutamine deamidase activity, we modified Pup with DON, a glutamine mimic produced by Streptomyces (21) that has been used to identify nucleophilic residues in glutamine-hydrolyzing enzymes (22,23). DON did not inhibit Dop-dependent amidohydrolysis in vitro (supplemental Fig.…”
Section: Pup-don Trap Reveals An Aspartate As a Potential Dopmentioning
confidence: 99%
“…Crystallographic analyses of microbial asparaginases and glutaminase-asparaginases have shown that they share the same basic structure and catalytic mechanism. 60 Glutamine Some microbes produce a periplasmic or extracellular asparaginase or glutaminaseasparaginase in addition to the intracellular asparaginase that participates in basic metabolism. [62][63][64][65] In the few cases where both enzymes have been studied, the two forms of asparaginase are similar in primary amino acid sequence and protein structure, but differ in other characteristics like pH and temperature activity profiles and, most notably, in substrate affinity.…”
Section: Asparaginasementioning
confidence: 99%